Повороткість МТА на основі орно-просапного трактора - Кюрчев, Володимир Миколайович; Kiurchev, Volodymyr (My University, 2014)
UA: Запропоновано методику оцінки повороткості машинно-тракторних агре-гатів на основі орно-просапного трактора серії ХТЗ-160. /// EN: The method estimation of agility is offered towed machine - tractor aggregates on the basis of the arable-cultivated tractor series XT3-160.
Agility of MTU on the basis of the arable-cultivated tractor
Keywords: машино-тракторний агрегат; радіус повороту; кривизна; tractor units; turning radius of curvature